Bibliometric study of research trends in dysphagia complicating following anterior cervical spine surgery - Qisong, Shang; Wei, Xiang; Yuanyuan, Wu; Xinghua, Song (Frontiers in Surgery, 2025)
BackgroundThe aim of this study was to assess the global research status and trends in the occurrence of dysphagia after cervical spine surgery using bibliometrics.MethodsAll relevant research publications on dysphagia occurring after cervical spine surgery were retrieved from the Web of Science Core Collection database. Literature coupling, co-citation and co-occurrence analyses were subsequently visualised using VOSviewer, CiteSpace. WPS Office was applied for data summary processing.ResultsBetween 2000 and 2023, a total of 477 clinical studies met the inclusion criteria. The number of global publications has steadily increased in four stages over the last 19 years, with the United States having the most publications (=194), followed by China (=134) and South Korea (=34). The most contributing institutions were UNIVERSITY OF CALIFORNIA SYSTEM in the USA (n = 24) and SICHUAN UNIVERSITY in China (n-21). The most distinguished scholar was Liu,Hao (n = 15), followed by Albert (n = 10) and Yang,Yi (n = 9). Ten of the most cited papers were cited more than 65 times. The most important journal for research on the occurrence of dysphagia after cervical spine surgery was SPNIE (n = 445), followed by EUR SPINE J (n = 337) and SPINE J (n = 322), which analysed a number of factors including anatomy, patient information and the use of inbuilt objects. The top 20 most commonly used keywords were identified from 750 author keywords, with the highest number being dysphagia (n = 303), followed by fusion (n = 183) and spine surgery (182). In parallel with time zone and cluster analysis we found multiple high frequency keywords that appeared as early as 2006 and have continued to the present day, reflecting the enthusiasm of a large number of scholars who have researched this topic.ConclusionThis bibliometric study analyses the global research hotspots and trends in postoperative cervical spine complication dysphagia in terms of study type, patient information, surgical modality, surgical segment, most popular keywords, most cited papers, journals, authors, institutions, and countries, to guide future practice and direction, in order to help understand how to effectively prevent or reduce the incidence of this postoperative complication so as to achieve the goal of lowering the patient's healthcare costs, to balance social medical resources and reduce the financial burden of the government.